A new tool to sense pH changes at the neuromuscular junction synaptic cleft - M. Blaustein (Nature Portfolio, 2020)
Abstract Synaptic transmission triggers transient acidification of the synaptic cleft. Recently, it has been shown that pH affects the opening of postsynaptic channels and therefore the production of tools that allow to study these behaviors should result of paramount value. We fused α-bungarotoxin, a neurotoxin derived from the snake Bungarus multicinctus that binds irreversibly to the acetylcholine receptor extracellular domain, to the pH sensitive GFP Super Ecliptic pHluorin, and efficiently expressed it in Pichia pastoris. This sensor allows synaptic changes in pH to be measured without the need of incorporating transgenes into animal cells. Here, we show that incubation of the mouse levator auris muscle with a solution containing this recombinant protein is enough to fluorescently label the endplate post synaptic membrane. Furthermore, we could physiologically alter and measure post synaptic pH by evaluating changes in the fluorescent signal of pHluorin molecules bound to acetylcholine receptors. In fact, using this tool we were able to detect a drop in 0.01 to 0.05 pH units in the vicinity of the acetylcholine receptors following vesicle exocytosis triggered by nerve electrical stimulation. Further experiments will allow to learn the precise changes in pH during and after synaptic activation.